Why Firm's Reactive Eco‐innovation May Lead to Consumers' Boycott. (26th February 2021) - Liao, Zhongju; Liu, Yan
Abstract: Firms that have implemented eco‐innovation are facing negative responses in the form of consumer boycotts. The intrinsic mechanism behind this phenomenon is worth studying. Based on psychological contract violation theory and attribution theory, and using psychological contract violation as the mediator variable and environmental concern as the moderator variable, this study constructs a relational model to explain why and how reactive eco‐innovation leads to consumer boycotts. The results indicate that firms' reactive eco‐innovation positively correlates with consumers' propensity to boycott consumer goods; reactive eco‐innovation can trigger consumers' boycott willingness through psychological contract violation, and consumer environmental concerns reduce the impact of psychological contract violation on consumer boycotts.